Characteristics of the force application point - a method to identify learning processes in alpine skiing? - Scheiber, P.; Schwameder, H.; Müller, E. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Since many years teaching concepts in alpine skiing are based on practice experiences and scientific research. Different tools are available to improve specific deficits. One of these tools is the so called "Alpine Basic Position" (ABP), which describes a particular body position. If one is trained in this, he is able to react on balance fluctuations, immediately. Furthermore it is possible to control movements in a harmonic and precise way, which is very important for steering skies exact and controlled. The determination of the force application point (FAP) is an important parameter to analyze body movements. In this study a fully qualified ski instructor (A) and an intermediate skier (B) were asked to fulfil five different exercises, which were developed for training the ABP. While A was skiing in a constant way, B was responding differently. Some exercises occurred a similar characteristic - in accordance to A -, some not.